Pathology for the health professions - Damjanov, Ivan (Elsevier/Saunders, 2012)
Presenting a foundation of pathology knowledge, this book gives you a concise and clinically relevant overview of general pathology, including injury, inflammation, and neoplasia, followed by a review of each organ system.